COMMUNICATION MANAGEMENT AGENT OF CHANGE IN THE STUDENT BULLYING PREVENTION PROGRAM AT SMP N 1 CITY OF GORONTALO - Ishak, Swesty Riani; Putri, Citra F.I.L Dano; PAKAYA, SITI MAYASARI; Mursalim, Muhammad Akram (Komunika, 2024)
Communication management is very important. for the process of reciprocal exchange of information, persuasion, or giving orders. This is used by agents of change so that they can carry out their duties of bullying prevention programs in schools. This study aims to explain the communication management of agents of change at SMP Negeri 1 Gorontalo City in the bullying prevention program. This is a qualitative study with data collection techniques using observation, interviews, and documentation. The findings show that the agents of change at SMPN 1 Kota Gorontalo carry out bullying prevention programs with several programs, such as bullying prevention programs through socialization, educational programs for each class, and programs through social media. Also, the top program of the anti-bullying campaign is carried out using communication management assisted by their supervisor as head of Counseling and Guidance. The conclusion from the findings is that the communication management of agents of change in the bullying prevention program at SMPN 1 Kota Gorontalo has been in accordance with the Cutlip and Center model of communication planning. As in the fact-finding process, agents of change have been able to identify bullying prevention programs well. In the planning process, even though in planning the bullying prevention program they still asked for help from the supervisor, they were able to carry out at the well by SMPN bullying the 1 Kota agents prevention of Gorontalo change programs by because well. they communicate The successful communication in through raising the process programs awareness is of those carried bullies have out implemented. However, in the final evaluation process, the agents of change do not carry out this process well. This is because they are still new so they do not know how the evaluation process is carried out.